ANALISIS PENGARUH KUALITAS SUMBER DAYA MANUSIA, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA GRAND CITYHALL MEDAN - Simbolon, Sahat (Jurnal Manajemen dan Bisnis, 2021)
This study aims to describe the effect of human resource quality, work discipline, and organizational culture on employee performance at Grand Cityhall Medan for 6 (six) months starting from May 2020 to November 2020. This study uses simple random sampling. The research subject was carried out on the employees of Grand Cityhall Medan. with a population of 439 people. The population study used a simple random sampling method. The instrument used was a questionnaire to collect data from the variables of the quality of human resources, work discipline, organizational culture, and employee performance. The data analysis technique used was the validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T-test, F-test, and determination coefficient tests. The results of the descriptive analysis in the variables of human resource quality, work discipline, and organizational culture are in the very good category, while the employee performance variables are in the very good category. The results of the descriptive analysis for the variables of human resource quality, work discipline, organizational culture, and employee performance are in the very good category, at Grand Cityhall Medan. Based on a partial analysis, the quality of human resources, work discipline, and organization has a positive and significant impact on employee performance at Grand Cityhall Medan. Simultaneously, the quality of human resources, work discipline, and organization have a positive and significant influence on employee performance at Grand Cityhall Medan. The contribution of the quality of human resources, work discipline, and organizational culture to improve employee performance variables is 0.975 or 97,5%, while the remaining 0.025 or 2,5% is from other variables not examined by the authors in this study, work environment, ethos. work, leadership, and so on.